Fidelity with plausibility : modest christologies in the twentieth century - Wildman, Wesley J., 1961- (State University of New York Press, 1998)
"The task of interpreting the religious significance of Jesus Christ takes shape in this book with the tension determined by two goals: fidelity to the classical Christological tradition, which draws our attention to Jesus in the first place, and plausability with respect to all forms of contemporary knowledge. To ignore the classical tradition is to assume uncritically that contemporary plausibility structures are beyond question, while to forsake plausibility is to embrace the irrationalism of the theological ghetto-dweller. This book argues that maintaining this tension in our time can be achieved only with a modest interpretation of Jesus Christ, one that repudiates the hermeneutical absolutism associated with affirming that Jesus Christ is uniquely, exhaustively, unsurpassably significant for revelation and salvation."--Jacket